(untitled) (Research, Society and Development, 2022)
In Brazil, the consumption of bread has occurred since the beginning of colonization in the 16th century, due to the eating habits of the Portuguese, and continues to this day. Several studies have been carried out with the aim of improving the nutritional value of breads, mainly in terms of protein content and quality, in addition to the content of minerals, vitamins and dietary fiber. One of the foods that has been widely used in this practice is pumpkin, through the use of its seeds, in the form of flour. The objective of this work was to produce and characterize a bread, made with the partial replacement of wheat flour with pumpkin seed flour (FSA) within a food and nutrition unit, and to evaluate its proximate composition and fiber content. After the production of pumpkin seed flour, a bread formulation was elaborated with substitution of 11% of the wheat flour for the pumpkin seed flour. The breads were submitted to chemical-nutritional composition analysis, where nutritional parameters were evaluated, with the following results: moisture (29.30%), carbohydrates (56.87%), lipids (4.39%), proteins (8.47%), ash (0.97%) and fibers (3.17%). Although the bread produced presented 300.79 Kcal, the product developed was considered a potential substitute for traditional French bread, given the nutritional properties found in the food.